Palladium Impurity Removal from Active Pharmaceutical Ingredient Process Streams. Issue 4 (1st October 2016) - Phillips, Stephanie; Holdsworth, Duncan; Kauppinen, Pasi; Mac Namara, Carl
In this article, we will look at palladium impurity removal from active pharmaceutical ingredient (API) process streams using metal scavengers and the drivers for the implementation of such processes. The article will review some of the available scavengers and detail how Johnson Matthey approaches the trial work and the methods used for screening, optimisation and scale-up of the scavenger process. It will outline the steps taken to ensure smooth transfer of the metal impurity removal process from lab to plant. This will include Johnson Matthey data from batch isotherm, kinetic and fixed bed trials and the application of mathematical models for performance characterisation and scale-up, which all feed into the final system design. Performance data for a number of the Johnson Matthey range of scavengers will be referenced both in batch and cartridge systems and the benefits of using the scavengers in a cartridge system will be presented.